IMPLEMENTATION OF TANJUNGBALAI REGIONAL REGULATION NO. 1/2015 ON QURAN LITERACY FOR MUSLIM STUDENTS FROM THE PERSPECTIVE OF FIQH SIYASAH - putra, Ilhamsyah; syam, syafruddin; Irwansyah, Irwansyah (Hukum tata Negara/Siyasah, 2025)
This study aims to examine whether Regional Regulation No. 1 of 2015 has been fully implemented. The questions asked include how the policy requiring Muslim students in elementary, junior high, and high schools to read and write the Qur'an is implemented and how the policy is evaluated from the perspective of fiqh siyasah. This study uses field research as its methodology. The results show that although the Regional House of Representatives approved the regulation in 2015, its implementation is still partial. Some schools are unaware of it, while others are aware but have not implemented it consistently due to scheduling conflicts. In the wider community, implementation also varies, with some schools aware of it and others not, possibly due to inconsistencies in government outreach.Keywords: Implementation, Local Regulations, Al-Qur'an Literacy, Fiqh Siyasah, Islamic Education, Tanjung Balai City.